(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study aims to determine the effect of using Whatsapp social media on employee communication performance at the South Sulawesi DPRD Provincial office. This study uses the theory of New Media (news media) and the theory of Uses and Gratifications (Usability and Satisfaction). The type of research used is quantitative research with the data collection process using a questionnaire. Primary and secondary data source types. Data collection techniques were carried out using Reliability techniques and Simple Linear Regression Analysis Techniques. The results of the study show that the variable use of social media WhatsApp (WA) has a significant effect on employee performance at the DPRD Secretariat Office of South Sulawesi Province. The regression coefficient is negative (-0.326) which means that the effect of using WA is negative on employee performance. This means that the higher the performance of using WA, the lower the performance of employees, and conversely the lower the use of WA, the higher the performance of employees.